Application of the Accelerated Learning Model to Increase Early Childhood Learning Motivation in Banana Kid's Kindergarten - Narsih; Nita Priyanti; Twi Endah; Mardianingsih; Siti Yasmin; Dewi Sartika (Universitas Panca Sakti Bekasi, 2023)
Early childhood education is very important, because the child's growth and development process is continuous until further development. This development process is determined by various simulations carried out by parents and teachers. In Banana Kid’s Kindergarten, the learning process is carried out through child-centered learning methods that are comfortable and can spark activeness in children so that children have an interest and enthusiasm (motivation) for learning that arises from the children themselves according to their wishes, therefore the purpose of this research was conducted to increase motivation. children's learning through the